2013
DOI: 10.1002/grl.50180
|View full text |Cite
|
Sign up to set email alerts
|

Shock compression of Fe‐FeS mixture up to 204 GPa

Abstract: [1] Using a two-stage light gas gun, we obtained new shock wave Hugoniot data for an iron-sulfur alloy ) over the pressure range of 94-204 GPa. A least-squares fit to the Hugoniot data yields a linear relationship between shock velocity D S and particle velocity u, D S (km/s) =3.60 (0.14) +1.57(0.05) u. The measured Hugoniot data for Fe-11.8wt%S agree well with the calculated results based on the thermodynamic parameters of Fe and FeS using the additive law. By comparing the calculated densities along the adia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 29 publications
4
33
1
1
Order By: Relevance
“…Similar densities and sound velocities were also obtained for liquid iron alloys by the more recent work of Huang et al [2011Huang et al [ , 2013, who suggested that the PREM density and velocity profiles in the outer core are consistent with liquid Fe-10 wt % S. Meanwhile, static compression measurements of liquid iron alloys are mostly limited to pressures below 5 GPa [Sanloup et al, 2000;Balog et al, 2003;Nishida et al, 2011]. The recent diamond anvil cell experiments by Morard et al [2013] obtained the density and bulk modulus of liquid Fe-Ni-S and Fe-Ni-Si alloys up to 94 GPa and 3200 K from the analysis of X-ray diffuse scattering, suggesting that a core composition containing 6 wt % of sulfur and 2 wt % of silicon matches the geophysical data.…”
Section: Introductionsupporting
confidence: 81%
“…Similar densities and sound velocities were also obtained for liquid iron alloys by the more recent work of Huang et al [2011Huang et al [ , 2013, who suggested that the PREM density and velocity profiles in the outer core are consistent with liquid Fe-10 wt % S. Meanwhile, static compression measurements of liquid iron alloys are mostly limited to pressures below 5 GPa [Sanloup et al, 2000;Balog et al, 2003;Nishida et al, 2011]. The recent diamond anvil cell experiments by Morard et al [2013] obtained the density and bulk modulus of liquid Fe-Ni-S and Fe-Ni-Si alloys up to 94 GPa and 3200 K from the analysis of X-ray diffuse scattering, suggesting that a core composition containing 6 wt % of sulfur and 2 wt % of silicon matches the geophysical data.…”
Section: Introductionsupporting
confidence: 81%
“…The binaries are calculated for two O and Si concentrations and show that increasing light element concentration in iron always decreases density, as observed in previous simulations (Badro et al, 2014;Brodholt & Badro, 2017;Umemoto & Hirose, 2015). It is striking that both calculations produce identical results, proving that the generally assumed hypothesis of ideal mixing of volumes (Badro et al, 2014;Brodholt & Badro, 2017;Huang et al, 2013) of binaries is indeed valid at CMB conditions. As for ternaries, the volumes (and densities) were calculated in two ways: one was by actual MD simulations on the previously described ternary compositions (Fe 90 Si 9 O 9 and Fe 86 Si 11 O 11 ) and one by mixing the binaries according to equation (5).…”
Section: Mixing Properties and Idealitysupporting
confidence: 65%
“…Ideal mixing has been the standard working hypothesis in this kind of study (6,19,22) and will need to be verified by future work. However, our study reinforces this hypothesis by showing that (i) the binary systems are perfectly ideal (as can be seen by the perfectly linear fits of density versus concentration) and (ii) our calculations were compared with existing shockwave data (19,(22)(23)(24) on molten Fe, Fe-O, and Fe-S alloys and found them to be in excellent agreement (SI Appendix, section 3).…”
mentioning
confidence: 94%
“…Ideal mixing has been the standard working hypothesis in this kind of study (6,19,22) and will need to be verified by future work. However, our study reinforces this hypothesis by showing that (i) the binary systems are perfectly ideal (as can be seen by the perfectly linear fits of density versus concentration) and (ii) our calculations were compared with existing shockwave data (19,(22)(23)(24) on molten Fe, Fe-O, and Fe-S alloys and found them to be in excellent agreement (SI Appendix, section 3). It should also be noted that high-pressure experiments have shown that miscibility gaps vanish at high pressures (25)(26)(27)(28), hence also indicating that high-density liquids tend to have a simpler thermodynamic behavior than their low-pressure counterpart.…”
mentioning
confidence: 94%